Предмет: Математика,
автор: Аноним
Упростите выражение: 3(х-2у)-0.5(2х+3у)-4.5х
Р.S.: решать не надо, просто расставьте Х - с Х, Y - с Y, и все.
Ответы
Автор ответа:
0
3(х-2у)-0.5(2х+3у)-4.5х=3x-6y-x-1,5y-4,5x=-2,5x-7,5y
Автор ответа:
0
а как появилась 3Х и 6у? Если не трудно)
Автор ответа:
0
3*x=3x: 3*2y=6y; ;; 0,5*2x=1x=x;;;;;0,5*3y=1,5y
Похожие вопросы
Предмет: Физкультура и спорт,
автор: ClarisVerbis
Предмет: Биология,
автор: munskaya
Предмет: Право,
автор: tatarova1980
Предмет: Математика,
автор: АбакумоваДарья